Identifying habitat use of Ursus arctos, Lynx lynx martinoi and Canis lupus lupus in Albanian forests using occupancy modelling - Laze, Kuenda (Hacquetia, 2020)
Forests are the principal terrestrial ecosystem for protected and endangered large carnivores, providing the main habitat for species maintenance and survival. Changes in forest cover influence species distribution. The aim was (1) to test hypotheses on the natural environmental (abiotic) and biological (biotic) factors and human disturbances that determine the colonization and local extinction of three large carnivore species in relation to forest cover, (2) to infer the biotic interactions between these three large carnivore species occupying the same forested areas in Albania. Colonization is estimated to be positively affected by forest cover for brown bear, Balkan lynx and grey wolf. Brown bear and grey wolf tend to compete for the same forested areas. Local extinction increased with decreasing forest cover for brown bear and increased with decreasing mixed broadleaved forests for Balkan lynx. Anthropological variables (proximity to villages and to neighbourhood roads) increased local extinction for brown bear, grey wolf and Balkan lynx. Further studies are recommended for better understanding biotic interactions of large carnivore species in forest habitats in Albania and its neighbouring countries, which could contribute to conservation of large carnivore species on a large scale.